THE MEDIATING ROLE OF TEACHING PROFESSION PERCEPTION IN THE EFFECT OF TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) AND SOCIAL ENVIRONMENT ON TEACHER READINESS - Tasya G Sianturi; Saidun Hutasuhut (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study addresses the issue of teacher readiness among students enrolled in the Education Study Programs at the Faculty of Economics and Business, Universitas Negeri Medan, as teacher readiness is a crucial aspect of preparing qualified future educators. The study aims to examine the effects of Technological Pedagogical and Content Knowledge (TPACK) and the social environment on teacher readiness, with teaching profession perception serving as the mediating variable. A quantitative approach with a causal research design was employed. The population consisted of students from the Education Study Programs at the Faculty of Economics and Business, Universitas Negeri Medan, from the 2022 cohort. A total of 153 students were selected as the research sample. Data were collected using a questionnaire and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that TPACK and the social environment have positive and significant effects on teacher readiness. The social environment also has a positive and significant effect on teaching profession perception, while teaching profession perception has a positive and significant effect on teacher readiness. Furthermore, the mediation analysis reveals that teaching profession perception mediates the relationship between the social environment and teacher readiness. These findings suggest that TPACK, the social environment, and teaching profession perception are important factors in enhancing teacher readiness among students in education study programs.